Paternal care plasticity: males care more for early- than late-developing embryos in an arboreal breeding treefrog - Yuan-Cheng Cheng; Cai-Han Xie; Yu-Chen Chen; Nien-Tse Fuh; Ming-Feng Chuang; Yeong-Choy Kam (Frontiers in Zoology, 2024)
Abstract Background Parental care benefits offspring but comes with costs. To optimize the trade-off of costs and benefits, parents should adjust care based on intrinsic and/or extrinsic conditions. The harm to offspring hypothesis suggests that parents should invest more in younger offspring than older offspring because younger offspring are more vulnerable. However, this hypothesis has rarely been comprehensively tested, as many studies only reveal an inverse correlation between parental care and offspring age, without directly testing the effects of offspring age on their vulnerability. To test this hypothesis, we studied Kurixalus eiffingeri, an arboreal treefrog with paternal care. We first performed a field survey by monitoring paternal care during embryonic development. Subsequently, we conducted a field experiment to assess the prevalence of egg predators (a semi-slug, Parmarion martensi) and the plasticity of male care. Finally, we conducted a laboratory experiment to assess how embryo age affects predation by P. martensi. Results Our results showed that (1) male attendance and brooding frequency affected embryo survival, and (2) males attended and brooded eggs more frequently in the early stage than in the late stage. The experimental results showed that (3) males increased attendance frequency when the predators were present, and (4) the embryonic predation by the semi-slug during the early was significantly higher than in the late stage. Conclusions Our findings highlight the importance of paternal care to embryo survival, and the care behavior is plastic. Moreover, our results provide evidence consistent with the predictions of the harm to offspring hypothesis, as males tend to care more for younger offspring which are more vulnerable.